Gender, ageing and extended working life : cross-national perspectives - Ni Leime, Aine; Street, Debra; Vickerstaff, Sarah, 1956-; Krekula, Clary; Loretto, Wendy (Bristol, UK : Policy Press, 2017)
International contributors apply lifecourse approaches to understanding evolving definitions of work and retirement. They consider the range of transitions from paid work to retirement that are potentially different for women and men in different family circumstances and occupational locations, and offer solutions governments should consider to enable them to evaluate existing policies.--
Includes bibliographical references and index.
WorldShare provided record.
Keywords: Life span, productive; Retirement age